Rare Variants in Genes Associated With Cardiomyopathy Are Not Common in Hypoplastic Left Heart Syndrome Patients With Myocardial Dysfunction - Helle, Emmi; Pihkala, Jaana; Turunen, Riitta; Ruotsalainen, Hanna; Tuupanen, Sari; Koskenvuo, Juha; Ojala, Tiina (Frontiers in Pediatrics, 2020)
Myocardial dysfunction is a known risk factor for morbidity and mortality in hypoplastic left heart syndrome (HLHS). Variants in some transcription factor and contractility genes, which are known to cause cardiomyopathy, have previously been associated with impaired right ventricular function in some HLHS patients. The care of HLHS patients is resource demanding. Identifying genetic variants associated with myocardial dysfunction would be helpful in tailoring the follow-up and therapeutic strategies. We tested whether a commercial cardiomyopathy gene panel could serve as a diagnostic tool in a Finnish cohort of HLHS patients with impaired right ventricular function to identify potentially pathogenic variants associated with poor prognosis. None of the patients had pathogenic or likely pathogenic variants in the studied cardiomyopathy-associated genes. Thus, our approach of performing a cardiomyopathy gene panel to identify pathogenic variants as directly causal or as modifiers for worse outcomes in hypoplastic left heart syndrome is not useful in clinical practice at the moment.